PERSPEKTIF IDEOLOGI DALAM WACANA SILANG TUTUR "KONVENSI PARTAI GOLKAR" - R, Syahrul (Diksi, 2005)
The study on the ideological perspective in this articleuses a critical discourse analysis that views discourse as action byconsidering certain context, historical context, element of power,and ideology. The material of analysis consists of newspaper reportsabout the discourse coming from various figures during the time ofthe Golkar Party Convention from its beginning to Wiranto's electionas the presidential candidate nominated by the party. The articleshows the emergence, in the reports, of various pro- and contraconventionperspectives coming from figures outside the party aswell as various ideological perspectives brought up by party figuresin their attempts to win the convention as the presidential candidatenominated by the party.Keywords: ideological perspective, party convention, criticaldiscourse analysisA. Pendahuluan